Flame assisted chemical vapour deposition NiO hole transport layers for mesoporous carbon perovskite cells. Issue 42 (15th October 2019) - Yates, Heather M.; Meroni, Simone M. P.; Raptis, Dimitrios; Hodgkinson, John L.; Watson, Trystan M.
Abstract : An industrially compatible in-line coating method has been used to deposit porous NiO transport layers to enhance perovskite cell performance. Abstract : Flame assisted chemical vapour deposition was utilised to directly deposit polycrystalline mesoporous NiO to enhance charge transport within carbon perovskite solar cells (C-PSC). This versatile technique is highly suited for deposition of large area thin films along with the ability to use simple, stable aqueous salts. The combination of low cost methods of screen printing and FACVD to produce the C-PSC make this an attractive route towards commercialisation. The effects of deposition parameters on the morphology, crystallinity and density of the deposited NiO are discussed, along with the importance of use of a low propane, 'lean flame' on both the NiO and underlying F-doped tin oxide electrode. The thickness of the NiO layer was found to be critical in optimising the C-PSC efficiency. Addition of the NiO layer resulted in an increased short circuit current density (17.30 mA cm −2 to 20.28 mA cm −2 ). At an estimated NiO thickness of 17 nm the average cell efficiency (10.73%) surpassed that of the control sample (9.08%) so confirming the promise of this technique.